Flocculation behavior of colloidal suspension by use of inorganic and polymer ﬂocculants in powder form - Kadooka, Hiroto; Kiso, Yukari; Goto, Shotaro; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (Elsevier, 2017)
The clariﬁcation method by using composite dry powdered ﬂocculants consisting of inorganic ﬂocculant, polymer ﬂocculant and ﬂocculation aid has been proposed in the literature. Such composite ﬂocculants are conveniently used in the ﬂocculation process of small volume suspensions; i.e. the composite dry powdered ﬂocculants are added directly to a suspension. However, very limited work has been reported on the ﬂocculation behavior when composite ﬂocculants are used in powder form. In this study, the eﬀect of both dosages of dry powdered inorganic ﬂocculant and ionic polymer ﬂocculant on turbidity removal of PMMA suspension is investigated. Floc characteristics, such as sludge volume and ﬂoc strength, are also discussed. It is found that there exist various combinations of inorganic and polymer ﬂocculant dosages resulting in suﬃcient turbidity removal; as the dosage of inorganic ﬂocculant is increased, the suitable dosage of ionic polymer ﬂocculant is also increased for better turbidity removal. Among these combinations of inorganic and polymer ﬂocculant dosages, ﬂoc strength in higher dosages is larger than that in lower dosages. It is also found that in the higher polymer dosage conditions, ﬂocculated sludge shows both local minimum and local maximum volume depending on dosage of inorganic ﬂocculant. From these results, variations of polymer ﬂocculant morphology under various inorganic ﬂocculant dosages are discussed. A procedure for determining the optimum composition of a composite dry powdered ﬂocculant for turbidity removal is proposed.